Generative AI for Students: the essential guide to using artificial intelligence for study at university - Meechan, David (London; Thousand Oaks, California: Sage, 2025)
"Using generative artificial intelligence as a student can be confusing and challenging. This authoritative guide equips you with practical knowledge, enabling you to leverage generative AI as a powerful study aid and embark on your academic journey with confidence. Exploring a wide spectrum of topics, from demystifying jargon and fostering critical thinking to addressing diversity, inclusion and academic integrity, this book is an essential companion for any higher education student looking to enhance their academic skill set and achieve success in their studies."-- Back cover.
Part 1. What you need to know about Generative AI -- Chapter 1. Navigating the AI landscape -- Chapter 2. What can generative AI do for your study skills? -- Chapter 3. Academic integrity and the ethical use of using generative AI at university -- Part 2. How to support your study with generative AI -- Chapter 4. Getting started with generative AI -- Chapter 5. Using generative AI tools to support your study -- Part 3. How to approach your assessments with generative AI -- Chapter 6. Essays -- Chapter 7. Presentations -- Chapter 8. Exams -- Chapter 9. E-portfolios -- Part 4. How to explore feedback with generative AI -- Chapter 10. Grades and feedback.
Keywords: Artificial Intelligence. -- Educational Applications; Study Skills; Artificial Intelligence